2014
DOI: 10.1308/003588414x13824511649210
|View full text |Cite
|
Sign up to set email alerts
|

Primary myxoid chondrosarcoma of the breast

Abstract: Primary breast chondrosarcoma has been rarely reported in the literature. Conservative breast surgery has never been part of the management of previously reported cases. Surgery remains the mainstay management of such a disease as it is resistant to chemotherapy and radiotherapy. In this report, we present a case of rare primary myxoid chondrosarcoma of the breast that was managed successfully with a conservative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…By contrast, the study revealed a more severe prognosis for the patients that underwent simple lumpectomy. Notably, at the time of writing, a novel case report was published in the literature that used a similar conservative breast surgery approach ( 26 ), supporting the present approach of performing quadrantectomy instead of mastectomy.…”
Section: Discussionmentioning
confidence: 64%
“…By contrast, the study revealed a more severe prognosis for the patients that underwent simple lumpectomy. Notably, at the time of writing, a novel case report was published in the literature that used a similar conservative breast surgery approach ( 26 ), supporting the present approach of performing quadrantectomy instead of mastectomy.…”
Section: Discussionmentioning
confidence: 64%
“…Only 18 cases of primary breast chondrosarcoma have been reported in the literature between 1967 and 2014. Until 2013 the gold standard was a radical mastectomy [7] , and conservative breast surgery was never part of the management of the 16 reported cases; in 2014, two cases of quadrantectomy were reported in the literature [8] , [9] , but the benefits of radical mastectomy compared with a more conservative surgery have not been mentioned. Mastectomy was associated with lymphadenectomy in 4 cases, associated with grafting in one case [2] ; it was preceded by neoadjuvant chemotherapy(with partial responce) in one case [6] and was followed by adjuvant radiotherapy in three cases.…”
Section: Discussionmentioning
confidence: 99%
“…The present case report describes a new case of primary mammary chondrosarcoma: by analysing the nature of the neoplasm, its dimensions, its suprafascial localisation, the necessity of wide margins of resection, the dimension of the breast, and the young age of the patient, and considering the absence of extra-lymph nodal and lymph nodal metastasis, it was decided to perform a skin-nipple-sparing mastectomy with the insertion of a mammary expander, rather than a definitive prosthesis, to allow the patient to undergo adjuvant radiotherapy. This surgical approach and the adjuvant radiotherapy were chosen with the consideration that the rare histological “myxoid chondrosarcoma” pattern of the tumour makes it chemoresistant [8] , and that hormone therapy has no rule in the treatment of pure mammary sarcomas. This fact is supported by immunohistochemical studies: the mesenchymal elements are positive both for S-100 and vimentin, but negative for common epithelial markers, such as cytokeratins and oestrogen and progesterone receptors [7] , [11] .…”
Section: Discussionmentioning
confidence: 99%